ESG-Based Financial Management and Sustainable Tourism Development: JEL Classification: G32; L83; M14; Q01; Q56 - Nicholas Fernando; Melissa Hartono (Mustard Journal De Ecobusin, 2026)
This study examines the role of ESG-based financial management in supporting sustainable tourism development. The research aims to analyze how environmental responsibility, social inclusion, and governance accountability influence tourism sustainability and institutional resilience. A qualitative case-study approach was employed through semi-structured interviews, field observations, and document analysis involving tourism authorities, tourism business managers, local communities, sustainability consultants, and environmental organizations. The findings reveal that ESG integration significantly influences tourism financial governance through sustainable investment allocation, environmental conservation initiatives, participatory governance, and transparency mechanisms. The study also demonstrates that ESG-oriented financial management strengthens destination competitiveness, stakeholder trust, and long-term tourism resilience. The findings contribute theoretically to sustainable tourism and ESG governance literature while providing practical implications for tourism policymakers, investors, and tourism organizations regarding sustainability-oriented financial planning and governance accountability. The study emphasizes that sustainable tourism competitiveness increasingly depends on collaborative governance, environmental responsibility, and transparent financial management systems.